2022
DOI: 10.1371/journal.ppat.1010468
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer and CoV-2 spike-immune complexes contribute to the production of PGE2 and proinflammatory cytokines in monocytes

Abstract: An overreactive inflammatory response and coagulopathy are observed in patients with severe form of COVID-19. Since increased levels of D-dimer (DD) are associated with coagulopathy in COVID-19, we explored whether DD contributes to the aberrant cytokine responses. Here we show that treatment of healthy human monocytes with DD induced a dose dependent increase in production of pyrogenic mediator, Prostaglandin E2 (PGE2) and inflammatory cytokines, IL-6 and IL-8. The DD-induced PGE2 and inflammatory cytokines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…It is now widely recognized that endothelial dysfunction and micro-thromboses play a significant role in acute infection and we see further evidence of this with our finding that D-dimer is positively correlated with circulating levels of total plasma Spike protein (p=0.0249) and EV-associated Spike protein (p<0.01) across all three groups of acute COVID-19 severity. D-dimer is a marker of coagulopathy 30, 31 and is highly correlated with the COVID-19 disease severity 32, 33 . Park et al 32 recently reported that D-Dimer can also form immune complexes with SARS-CoV-2 Spike protein and bound antibodies resulting in activation of monocytes to produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely recognized that endothelial dysfunction and micro-thromboses play a significant role in acute infection and we see further evidence of this with our finding that D-dimer is positively correlated with circulating levels of total plasma Spike protein (p=0.0249) and EV-associated Spike protein (p<0.01) across all three groups of acute COVID-19 severity. D-dimer is a marker of coagulopathy 30, 31 and is highly correlated with the COVID-19 disease severity 32, 33 . Park et al 32 recently reported that D-Dimer can also form immune complexes with SARS-CoV-2 Spike protein and bound antibodies resulting in activation of monocytes to produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer is a marker of coagulopathy 30, 31 and is highly correlated with the COVID-19 disease severity 32, 33 . Park et al 32 recently reported that D-Dimer can also form immune complexes with SARS-CoV-2 Spike protein and bound antibodies resulting in activation of monocytes to produce proinflammatory cytokines. Moreover, endothelial dysfunction may be caused by both direct infection of endothelial cells 34 and by the SARS-CoV-2 components in the bloodstream 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased level of PGE 2 in the plasma of COVID-19 patients associated with disease severity, due to its immunosuppressive effect and the disruption of the immune response. 43 , 44 Interestingly, our finding exhibited twofold reduction of PGE 2 level in lung tissues at day 4 post-infection. Thus, fingerroot extract could suppress inflammatory cytokine production in the infected hamsters.…”
Section: Discussionmentioning
confidence: 50%
“…We experimentally tested seven selected compounds that inhibit the VIPs BRD4, IMPDH2 and HDAC2, along with spautin-1, which inhibits the NIP USP10 and the VIP USP13 ( Table 2 ). The compounds were first tested for modulation of SARS-CoV-2 infection in HEK293T cells that overexpress the key SARS-CoV-2 host factors ACE2 and TMPRSS2 [ 32 ]. Confirmatory experiments were performed in Calu 3 human lung cells [ 33 ], which are well-established targets for SARS-CoV-2 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%